Inhibitor of growth 3 induces cell death by regulating cell proliferation, apoptosis and cell cycle arrest by blocking the PI3K/AKT pathway. (October 2018) - Zhao, Song; Wang, Long; Zhang, Chunmei; Deng, Yu; Zhao, Bai; Ren, Yuxin; Fu, Yingmei; Meng, Xianzhi
Abstract ING3 is a potential candidate tumor-suppressor gene that has been implicated in the pathogenesis of various cancers, however the exact role and mechanism of ING3 in gastric cancer (GC) remains elusive. In this study, the low expression of ING3 was validated in GC tissues and various GC cell lines. Overexpression of ING3 by transfection with pEGFP-ING3 plasmids inhibited cell proliferation in SGC-7901 and BGC-825 cells, concomitant with the decrease in the expression of PCNA, a marker for cell proliferation. Furthermore, overexpression of ING3-induced cell cycle arrest at G2 /M phase. Meanwhile, elevation of ING3 distinctly aggravated cell apoptosis and increased Bax and Caspase-3 expression, but decreased Bcl-2 expression. Moreover, ING3 upregulation inhibited the activation of the PI3K/AKT pathway by reducing the expressions of p-PI3K and p-Akt in GC cells. Notably, preconditioning with IGF-1, a PI3K/Akt agonist, reversed the suppressive effects of ING3 overexpression on GC cell growth, cell cycle arrest and apoptosis. Furthermore, IGF-1 attenuated the inhibitory effect of excessive ING3 on CyclinD1 expression. Taken together, these results suggest ING3 may function as a tumor-suppressor gene in the progression of GC. Therefore, ING3 could serve as a potential therapeutic strategy for the treatment of GC.